Genome-Wide Transcription Analysis of Electroacupuncture Precondition-Induced Ischemic Tolerance on SD Rat With Ischemia–Reperfusion Injury - Fu, Shuping; Yu, Meiling; Xu, Houxi; Liu, Qing; Li, Xiaoxiao; Wang, Yaling; Chen, Yonglin; Meng, Lingling; Qiu, Yiting; Jing, Xinyue; Liu, Chenchen; Lu, Shengfeng (Frontiers in Genetics, 2021)
Acupuncture promotes the recovery of neurological function by the overall improvement of ischemic brain injury. It is not only regarded as a rehabilitative treatment but also a pretreatment method for stroke. However, its mechanism has not been fully elucidated. In this study, rats were treated with electroacupuncture (EA) at Baihui (GV20) for 30 minutes/day for six days, ahead of conducting cerebral ischemia-reperfusion (I/R) injury. Infarction volume, Evans blue leakage, and neurological deficits were evaluated at 24h after I/R injury. Then, the ipsilateral ischemic brain was isolated for RNA-Seq to identify molecular consequences. The results showed that EA pretreatment decreased blood-brain barrier permeability, reduced brain infarction volume, and improved neurological outcomes. EA pretreatment could up-regulate anti-virus and immunity activity-associated genes (such as Ifit1, Ifit3, Irf7, Oasla, etc.) and downregulate matrix disruption-associated genes (Col24a1, Col11a1, Col27a1, etc.) expressions of the healthy rats. In addition, it could partially reverse or ameliorate genome-wide transcription changes of the ipsilateral ischemic brain. For the first time, this study provides insight into genomic network modulation of the healthy rat with EA treatment and the EA preconditioning rat under subsequent IR injury, which is helpful to explain acupuncture precondition-induced ischemic tolerance of stroke. It also provides new strategies and targets for the prevention of ischemic stroke.